Phylogenomics of Salvia L. subgenus Calosphace (Lamiaceae) - Lara-Cabrera, Sabina Irene; Perez-Garcia, Maria de la Luz; Maya-Lastra, Carlos Alonso; Montero-Castro, Juan Carlos; Godden, Grant T.; Cibrian-Jaramillo, Angelica; Fisher, Amanda E.; Porter, J. Mark (Frontiers in Plant Science, 2021)
The evolutionary relationships of Salvia have been difficult to estimate. We used the Next Generation Sequencing method Hyb-Seq to evaluate relationships among 90 Lamiaceae samples, including representatives of Mentheae, Ocimeae, Salvia subgenera Audibertia, Leonia, Salvia, and 69 species of subgenus Calosphace, representing 32 of Epling’s sections. A bait set was designed in MarkerMiner using available transcriptome data to enrich 119 variable nuclear loci. Nuclear and chloroplast loci were assembled with hybphylomaker (HPM), followed by coalescent approach analyses for nuclear data (ASTRAL, BEAST) and a concatenated Maximum Likelihood analysis of chloroplast loci. The HPM assembly had an average of 1,314,368 mapped reads for the sample and 527 putative exons. Phylogenetic inferences resolved strongly supported relationships for the deep-level nodes, agreeing with previous hypotheses, subgenus Audibertia is sister to subgenus Calosphace; within subg. Calosphace we recovered eight monophyletic sections sensu Epling, Cardinalis, Hastatae, Incarnatae and Uricae in all the analyses (nDNA and cpDNA), Biflorae, Lavanduloideae and Sigmoideae in nuclear analyses (ASTRAL, BEAST) and Curtiflorae in ASTRAL trees; network analysis supports deep node relationships, some of the main clades and recovers reticulation within the core Calosphace. The chloroplast phylogeny resolved deep nodes and four monophyletic Calosphace sections. Placement of S. axillaris is distinct in nuclear evidence and chloroplast, as sister to the rest of S. subg. Calosphace in chloroplast and in a clade with 'Hastatae clade' sister to the rest of the subgenus in nuclear evidence. We also tested the monophyly of S. hispanica, S. polystachia, S. purpurea, and S. tiliifolia including two samples of each and found that S. hispanica and S. purpurea are monophyletic. Our baits can be used in future studies of Lamiaceae phylogeny to estimate relationships between genera and among species. Here we present a Hyb-Seq phylogeny for complex, recently diverged Salvia, which could be implemented in other Lamiaceae.